'Mutants of the 67th parallel north' : Punk performance and the transformation of everyday life - Pilkington, Hilary (Punk & Post Punk, 2012)
On a hand-made poster in the ‘HQ’ of the Biker Club in Vorkuta, the three members of the local punk band Mazut loom out of the darkness, their faces comically distorted and framed either side by the words ‘Fucking noise’ and ‘Mutant-morons’. This article traces tropes of ‘mutation’, ‘mutant’ and ‘moron’ within the music, performance and self-identifications of punk scene members drawing on interviews, field notes, audio and visual recordings gathered in autumn 2009 in the city of Vorkuta in Russia’s far North. It explores the ‘mutant’ hero as it appears in facial and bodily gestures, song lyrics and everyday talk on the punk scene. It considers the meanings attached to the practice of ‘mutation’ among scene members as well as the unarticulated role it plays in signalling a boundary crossing between ‘everyday life’, marked by heavy physical and emotional demands of routines of paid employment and family lives, and ‘subcultural life’, as a practice of the enactment of (a consciously temporary) freedom from them.